Anthropometric profile in different event categories of acrobatic gymnastics - Taboada-Iglesias, Y.; Vernetta Santana, M.; Gutierrez-Sanchez, A. (Journal of Human Kinetics, 2017)
There is a specific anthropometric profile for each sport, which may be differentiated even in relation to the position, role or event category within each sport discipline. However, there are few studies on acrobatic gymnastics, and the goal of this work was to determine the anthropometric profile depending on the event category, as well as factors that predisposed to performance in these categories. The sample consisted of 150 gymnasts from Spain, divided into 8 groups according to the event category and the role played. The kinanthropometric measurements were taken through the procedures established by the International Society for the Advancement of Kineantropometry. The anthropometric characteristics, including body mass index, somatotype, body composition and proportionality using the Phantom stratagem were analyzed, and the results obtained from the different groups were compared. A regression analysis was performed with particular groups of gymnasts. No significant differences (p < 0.05) were observed between groups of female tops or male bases, although differences were found between female group bases and female pair bases. It could be suggested that higher values of body height, sitting height, the minimum abdominal circumference, percentage of fat and low biliocristal breadth predispose female bases to work in pairs rather than in groups. The conclusion is that the anthropometric measurements are not decisive when guiding a gymnast toward choosing one event category or another, except for female bases.